Análise do impacto da utilização do transporte elétrico coletivo no sistema elétrico de distribuição - Baldissera, Luciano Bonato (2016)
The collective electric transport can be considered as one of the best alternatives to reduce the concentration of pollutants in urban centers, because it reduces the number of vehicles in circulation and eliminates most of the problems arising from the use of fossil fuels. Currently, in this alternative, there is a wide range of options available, however, with the advancement occurred in recent years in terms of battery technology, the pure electric bus has stood out due to advantages related to its flexibility, sustainability and adaptability to the existing infrastructure. However, the use of these vehicles requires special recharging stations, which drain a lot of energy of the grid, in a short time, a feature that generates a significant impact on electrical systems. Moreover, the high amount of energy required for the operation of these vehicles precludes the use of technology in certain places, because it requires large investments in infrastructure for power supply, which often do not is available locally in the short term. Based on this, this dissertation presents a study of the impact generated in the electrical distribution system caused by the replacement of a diesel bus fleet by electric buses in a small town in southern Brazil. The study was based on the measurement of energy consumption through data related to the lines and the vehicle driving cycle, applied to an electric bus model, it was developed with Matlab software. Actual data of the lines was used, as distance, speeds, tilt, number of passengers, among others, obtained through a GPS equipment and information provided by the company analyzed. At the end were generated values related to the energy consumption of vehicles in each of the lines, the electricity consumption increase generated by the substitution in question and an estimate of the daily load curves based on the operating hours of the analyzed lines.